The paradigm shift: Heartbeat initiation without “the pacemaker cell” - Maltsev, Victor A.; Stern, Michael D. (Frontiers in Physiology, 2022)
The current dogma about the heartbeat origin is based on “the pacemaker cell”, a specialized cell residing in the sinoatrial node (SAN) that exhibits spontaneous diastolic depolarization triggering rhythmic action potentials (APs). Recent high-resolution imaging, however, demonstrated that Ca signals and APs in the SAN are heterogeneous, with many cells generating APs of different rates and rhythms or even remaining non-firing (dormant cells), i.e. generating only subthreshold signals. Here we numerically tested a hypothesis that a community of dormant cells can generate normal automaticity, i.e. “the pacemaker cell” is not required to initiate rhythmic cardiac impulses. Our model includes (i) non-excitable cells generating oscillatory local Ca releases and (ii) an excitable cell lacking automaticity. While each cell in isolation was not “the pacemaker cell”, the cell system generated rhythmic APs: the subthreshold signals of non-excitable cells were transformed into respective membrane potential oscillations via electrogenic Na/Ca exchange and further transferred and integrated (computed) by the excitable cells to reach its AP threshold, generating rhythmic pacemaking. Conclusions: Cardiac impulse is an emergent property of the SAN cellular network and can be initiated by cells lacking intrinsic automaticity. Cell heterogeneity, weak coupling, subthreshold signals, and their summation are critical properties of the new pacemaker mechanism, i.e cardiac pacemaker can operate via a signaling process basically similar to that of “temporal summation” happening in a neuron with input from multiple presynaptic cells. The new mechanism, however, does not refute the classical pacemaker cell-based mechanism: both mechanisms can co-exist and interact within SAN tissue.